PPO.31 First trimester bacterial vaginosis is associated with mid-gestation short cervical length and positive fFN test, and spontaneous preterm birth in high risk women. (9th June 2014) - Nwokoro, I; Forya, F; Warner, D; Fox, G; Greenwold, N; Raghwani, JL; Morris-Jones, S; David, AL; James, CP
Abstract : Background: Screening and treatment for abnormal vaginal flora may reduce the risk of spontaneous preterm birth (sPTB) by 47% in the general antenatal population. 1 We investigated the association between bacterial vaginosis (BV), markers of sPTB risk and pregnancy outcome in women attending a PTB clinic due to history of sPTB, late miscarriage or cervical surgery Methods: Women attending the UCLH PTB clinic (2008–2013) were identified from the prospective clinic database. Cervical length (CL), fetal fibronectin (fFN), and pregnancy outcome data were extracted. First trimester vaginal swab results were confirmed with electronic microbiology records. Data were analysed using z-ratios and Mann-Whitney-U tests. Results: 805 of 1240 women (65%) were screened for BV, with pregnancy outcomes available for 722 women. Swabs were positive in 5% (n = 38) women screened. Women with BV were more likely to have sPTB (<37 weeks) when compared with women without BV (36%, n = 13 vs 19%, n = 132, z = 2.484, p = 0.013). Median gestation at delivery for women with BV was 37+6 weeks (20+2–41+4) compared with 39+0 (16+2–42+5) for women without BV (p = 0.0074). CL and fFN results were available for 791 and 574 women respectively. Women with BV were more likely to test positive for fFN (>50ng/ml) than those without BV (27%, n = 7 vs 13%, n = 72, z = 1.972, p = 0.0486) and had a shorter median CL (21 mm, 1–45 vs 27 mm, 0–50, p = 0.0096). Conclusion: BV in the first trimester is associated with a short cervix and positive fFN test in the second trimester and sPTB in women at risk of preterm birth. Reference: Sangkomkamhang US, Lumbiganon P, Prasertcharoensook W, Laopaiboon M. Antenatal lower genital tract infection screening and treatment programs for preventing preterm delivery. Cochrane Database of Systematic Reviews 2008, Issue 2. Art. No.: CD006178. DOI: 10.1002/14651858. CD006178.pub2